Investigation of the momentum compaction factor of the ESR thorough Schottky mass measurements. (26th November 2015) - Yan, X L; Bosch, F; Litvinov, Yu A; Nolden, F; Steck, M; Tu, X L; Xu, H S; Zhou, X H; Zhang, Y H
Abstract: Schottky mass spectrometry was applied to stored and cooled neutron-deficient 152 Sm projectile fragments at the experimental storage ring (ESR) facility at GSI Darmstadt, Germany. 311 different nuclides were identified by means of their revolution frequency spectra. The measured frequencies were used to investigate the shape of the momentum-compaction-factor of the ESR.